Morphological and molecular identification of Eimeria rajasthani (coccidia: Eimeriidae) in the dromedary camel (Camelus dromedarius) in Riyadh, Saudi Arabia - Al-Shaebi, Esam M.; Al Quraishy, Saleh; Omer, Sawsan A.; Abdel-Gaber, Rewaida; Mohammed, Osama B. (Frontiers in Veterinary Science, 2024)
IntroductionCoccidiosis is a serious parasitic disease in camels caused by an intestinal protozoan parasite of the genus Eimeria, which is linked to significant causes of reduced milk and meat production. In Saudi Arabia, scare literature focused on the coprological investigation of dromedary camels (Camelus dromedarius). To determine the taxonomic status of camel parasite species, we performed morphological characterization of oocysts and genetic analysis (18S rRNA and ITS-1 gene regions) of Eimeria species collected from camels in Riyadh, Saudi Arabia.MethodsA total of 150 faecal samples were obtained from camels at the old camel market. These samples were tested for the presence of Eimeria oocysts using the conventional floatation technique before being sporulated in a 2.5% potassium dichromate solution. Eimeria oocysts were morphologically and molecularly examined and identified, and the infection rate of parasitic infections was determined.ResultsOur findings revealed that the overall frequency of oocysts was 30%. The identified species was Eimeria rajasthani, which had a typical ellipsoidal oocyst shape. Oocystic polar granule, micropyle, micropylar cap, and oocyst residuum are not visible. Sporocysts are oval with stieda body. Sporocyst residuum contains many granules and sporozoites with refractile bodies and nuclei. Genetic analyses of the sequence data from the partial 18S rRNA and ITS-1 gene regions revealed that the sequences obtained from E. rajasthani oocysts are related to DNA sequences reported from E. lamae from the Alpaca from China, particularly the 18S rRNA sequences.ConclusionThis study emphasized the need to use molecular phylogenetic tools to describe camel intestinal coccidian parasites with traditional morphology-based approaches to better understand their biology. For camel husbandry and disease control, more studies should be conducted to better understand the epidemiology of these protozoan parasites.